Analisis Pengendalian Persediaan Bahan Baku Keripik Pisang dengan Pendekatan Lot Sizing (Studi Kasus pada IRT. Tiga Saudara Bandar Lampung) - Wibowo, Heri ; Sidiq , Ahmad ; Supriono , Untung (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2018)
IRT Tiga Saudara was one of home industry in banana chips field product. Therefore it needed the one method to optimize the raw material inventory and decrease the order cost. The raw material inventory control could use lot sizing approach. The Result showed that accurate forecasting method was linear regression method, because it had Mean Absolute Deviation (MAD) was 510.416, so it was still in upper control limit and lower control limit after Moving Range chart test. The lot sizing method that had lowest total inventory was Economic Order Quantity (EOQ), with optimal order was 526 kg and it was ordered 72 many times during 12 period in one year, reorder point level when raw material before end was 299 kg. The safety stock was 73 kg, so that the total cost was Rp. 790.500,-.